The Role of Immigration in Prevention of Criminal Acts Trafficking in Humans - Dimas Prayoga; Mhd Azhali Siregar (International Journal of Law and Society, 2024)
The crime of human trafficking is a form of modern human slavery. Apart from that, the criminal act of human trafficking is one of the worst forms of treatment that violates human dignity. The rise of human trafficking crimes in various countries, including Indonesia and other developing countries, is a problem in itself for Indonesia. The international community and members of international organizations, especially the United Nations (UN). The emergence of human trafficking often occurs when someone is vulnerable, among whom the victims are often women and children who are categorized as weak. This research is also descriptive analysis, descriptive analysis is an attempt to describe or describe events and happenings without carrying out hypotheses and statistical calculations. Analytical descriptive is what the respondent states in writing or orally, as well as their real behavior, which is researched and studied in its entirety. Data collection was carried out using a documentation study where all secondary data used in this research was collected using this research. This research was carried out using data collection tools, namely: literature study or document study.Prevention carried out by Immigration to prevent the Crime of Human Trafficking, namely Immigration can prevent the Crime of Human Trafficking by increasing monitoring at borders, tightening the provision of passports, especially for people who are still of productive age to prevent them from becoming victims of the Crime of Human Trafficking abroad, Immigration officers take effective anticipatory steps by conducting further and in-depth interviews with passport applicants before deciding whether to approve or reject the issuance of a passport, increasing officer training to recognize signs of victims of human trafficking crimes, collaborating with international institutions and non-governmental organizations in the campaign against the Crime of Human Trafficking, as well as involving the community in this prevention effort